Identification of prognostic factors predicting outcome in Hodgkin's lymphoma patients relapsing after autologous stem cell transplantation† - Martínez, Carmen; Canals, C.; Sarina, B.; Alessandrino, E. P.; Karakasis, D.; Pulsoni, A.; Sica, S.; Trneny, M.; Snowden, J. A.; Kanfer, E.; Milpied, N.; Bosi, A.; et al. (Annals of oncology, 2013)
Background - High-dose chemotherapy followed by autologous stem cell transplantation (ASCT) is the standard of care for patients with relapsed Hodgkin's lymphoma (HL). However, there is currently little information on the predictors of outcome for patients whose disease recurs after ASCT. - Methods - Five hundred and eleven adult patients with relapsed HL after ASCT from EBMT-GITMO databases were reviewed. - Results - Treatments administered following ASCT failure included conventional chemotherapy and/or radiotherapy in 294 (64%) patients, second ASCT in 35 (8%), and alloSCT in 133 (29%). After a median follow-up of 49 months, overall survival (OS) was 32% at 5 years. Independent risk factors for OS were early relapse (<6 months) after ASCT, stage IV, bulky disease, poor performance status (PS), and age ≥50 years at relapse. For patients with no risk factors OS at 5 years was 62% compared with 37% and 12% for those having 1 and ≥2 factors, respectively. This score was also predictive for outcome in each group of rescue treatment after ASCT failure. - Conclusion(s) - Early relapse, stage IV, bulky disease, poor PS, and age ≥50 years at ASCT failure are relevant factors for outcome that may help to understand the results of different therapeutic approaches.
Gesehen am 23.06.2021